2016
DOI: 10.1248/yakushi.15-00252
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Plasma Levels of Anionic Uremic Toxins and Clinical Parameters in Hemodialysis Patients

Abstract: When the kidney is seriously impaired, various uremic toxins (UTs) accumulate in the body, often exerting unfavorable eŠects on physiological functions and drug pharmacokinetics. To prevent this, it is important to determine plasma UT levels accurately in chronic kidney disease patients. Although attempts to predict plasma UT levels using biomarkers have been made, the correlation between UT levels and the markers is not yet fully understood. In this study, we assessed the correlations among plasma levels of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…In order to access this, we first compared the correlation between serum IS levels and eGFR between the elderly with or without dementia. Consistent with previous studies, 21,22) there was a significant correlation between serum IS levels of 37 residents and their eGFR (Fig.1A). However, the r value was at most -0.420, indicating that the correlation between them was not so relevant.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In order to access this, we first compared the correlation between serum IS levels and eGFR between the elderly with or without dementia. Consistent with previous studies, 21,22) there was a significant correlation between serum IS levels of 37 residents and their eGFR (Fig.1A). However, the r value was at most -0.420, indicating that the correlation between them was not so relevant.…”
Section: Discussionsupporting
confidence: 92%
“…20) Accordingly, many interests have been placed on the blood IS levels in CKD patients and it has been suggested that eGFR is a useful parameter to roughly know blood IS levels. 21,22) However, little information is available about how the relationship between eGFR and serum IS levels changes in CKD patients when they suffer from various complications. It is well known that CD including dementia is frequent in CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, they believe that it is an indicator associated with better nutritional status and may be a marker of a healthy diet and omega 3 consumption. Its elevated serum levels in CKD patients were not associated with mortality and cardiovascular disease [102].…”
Section: Other Compoundsmentioning
confidence: 84%
“…The level of CMPF in serum was significantly higher after hemodialysis (27.3 ±1.8 mg/L) compared to pre-hemodialysis [32]. In contrast, it is known that the concentration of CMPF in plasma does not change before and after hemodialysis [101,102]. The ratio of CMPF binding to proteins is nearly 100% and this bond is stronger than for IS or PCS [99].…”
Section: Other Compoundsmentioning
confidence: 91%
“…On the other hand, there was no significant correlation between CP-1 and eGFR at all the cutoff CMPF concentrations. Ichimura et al 26 reported that plasma indoxyl sulfate concentration correlated negatively with eGFR in 20 patients on hemodialysis, whereas plasma CMPF concentration did not. Given the above results and evidence, plasma CMPF concentration may be a more prominent factor influencing OATP1B activity than eGFR.…”
Section: Discussionmentioning
confidence: 99%